2019
DOI: 10.1101/566968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Single-Cell Immune Atlas of Triple Negative Breast Cancer Reveals Novel Immune Cell Subsets

Abstract: 26Triple-negative breast cancer (TNBC) represents the most aggressive breast cancer 27 subtype, which recently attracts great interest for immune therapeutic development. In 28 this context, in-depth understanding of TNBC immune landscape is highly demanded. 29 Here we report single-cell RNA sequencing results of 9683 tumor-infiltrated immune 30 cells isolated from 14 treatment naïve TNBC tumors, where 22 immune cell subsets, 31 including T cells, macrophages, B cells, and DCs have been characterized. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Since studies on WES did not fully address the questions related to mBCs, there is a need to further explore this entity thanks to new technologies including single-cell sequencing, proteomics, and Assay for Transposase-Accessible Chromatin using sequencing (ATACseq). Preliminary studies have enabled to specify immune ecosystem of TNBC (83) and suggest that subclonal resistant cells pre-exist and can be selected by treatment (84). This approach is nevertheless dependent on the sampling, just as bulk sequencing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Since studies on WES did not fully address the questions related to mBCs, there is a need to further explore this entity thanks to new technologies including single-cell sequencing, proteomics, and Assay for Transposase-Accessible Chromatin using sequencing (ATACseq). Preliminary studies have enabled to specify immune ecosystem of TNBC (83) and suggest that subclonal resistant cells pre-exist and can be selected by treatment (84). This approach is nevertheless dependent on the sampling, just as bulk sequencing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated through high-resolution CLSM micrographs clustering of both cancer and stromal populations into non-uniform agglomerates and randomly distributed cells within both models was observable. Triple-negative breast cancer naturally showcases stromal/cancer cell clusters with semi-defined borders in which direct cell-cell interactions between cancer, stromal and immune cells are found to be highly recurrent [71,72]. Following the characterization of dECM-Spheroids size/shape, necrotic core establishment, cell viability, and spatiotemporal distribution of cancer cells and fibroblasts in coculture models, their utility to serve as a living platform for studying metastatic breast cancer cells invasion in vitro was investigated.…”
Section: Cell-ecm Architecture Of Decm-spheroidsmentioning
confidence: 99%
“…This may contribute to an elevated CD8_C03 (Tex) terminal exhausted signature score being associated with better prognosis in TCGA ovarian cohort. This may not be unique to ovarian cancer as Zhang and co-workers 47 reported that CD8-CXCL13 and CD4-CXCL13 T cells, which are proposed to represent exhausted T cells, predict effective responses to PD-L1 blockade in breast cancer. However, other studies suggest that dysfunctional T cells can no longer be reversed and activated by PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%